Patentability of Gene-Editing Technology and Clustered Regularly Interspaced Short Palindromic Repeats: Cases based legal Analysis - Waqas Younus; Shahid Abbas; Farheen Zehra (Journal of Peace, Development and Communication, 2024)
The study aims to evaluate the patentability of Gene-editing technology, specifically focusing on “Clustered Regularly Interspaced Short Palindromic Repeats (hereinafter CRISPR).” The qualitative and empirical methodologies,is adopted to examin fundamental criteria for patentability outlined in US patent law (2015) and the American Invents Act 2011. It draws on legal precedents, with a particular emphasis on key United States Supreme Court cases such as Alice v. CLS International Bank(2014) and Myriad Genetics, Inc. v. Molecular Pathology,(2013) to explore their practical implications on CRISPR technology. The significance lies in detailed analysis; how established legal standards affect the patentability of cutting-edge gene-editing technologies. By weaving together legal frameworks and real-world implications, the study provides a comprehensive understanding of the patentability landscape surrounding CRISPR. This sheds light on the complex interplay between legal considerations and technological advancements, which is crucial for stakeholders in the biotechnology and legal sectors. The study has potential recommendations for policymakers and legal practitioners on navigating the challenges associated with the patentability of gene-editing technologies and also suggests prospective revisions to current patent laws to better accommodate technological advancements that fosters balanced innovation while protecting intellectual property rights.